Communication Network of Digital Opinion Movement in the Formation of Personal Data Protection Regulation - Akhmad Kurniawan (Journal La Sociale, 2024)
The rise of data theft in the digital space has prompted the public to call for regulations regarding data security to be implemented immediately. Opinions in the form of requests for the passing of the Personal Data Protection Law (UUPDP) via social media Twitter have become very widely discussed. UUPDP is a regulation related to personal data protection to fill the regulatory void in the digital space. The keyword UUPDP became a topic of conversation on Twitter when the UUPDP personal data protection law was passed by the government and the DPR. The aim of this research is to map the Digital Opinion Movement through communication networks and identify influential actors in communication networks using the keyword UUPDP on Twitter. This research uses the Social Media Network Analysis (SMNA) method. The theory used to answer this case is the Digital Movement of Opinion/DMO theory and communication network theory. information collected via Twitter from 11 September 2022 – 21 September 2022. Stages in analyzing and retrieving data using the website based Netlytic.org application and Gephi software. The use of this tool is used to map influential actors involved in the communication network using UUPDP keywords, next to measure centrality using the indicators of degree centrality, betweenness centrality, closeness centrality and eigenvector centrality. The results of the research are 2 (two) main actors who influence the movement of digital opinion in communication networks with the keyword UUPDP, namely @franken_blues and @hunterjagar3.